2007
DOI: 10.1002/ijc.22536
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T‐cell function of adult T‐cell leukemia/lymphoma cells

Abstract: Adult T-cell leukemia/lymphoma (ATLL) patients are highly immunocompromised, but the underlying mechanism responsible for this state remains obscure. Recent studies demonstrated that FOXP3, which is a master control gene of naturally occurring regulatory T (Treg) cells, is expressed in the tumor cells from a subset of patients with ATLL. Since most ATLL cells express both CD4 and CD25, these tumors might originate from CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
65
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 21 publications
6
65
0
Order By: Relevance
“…Indeed, Foxp3 is not only a selective marker for a subset of ATLL but is also a possible pathogenic pathway of leukemia. [24][25][26]33 Foxp3 directly controls Treg cell function by interacting with the transcription factor AML1 and the Runx1 to suppress IL-2 and IFN-g production, upregulate Treg cell-associated molecules and exert suppressive activity. 27,34,35 The new antisense strategy, RNA interference (RNAi), is one of the most potent.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Foxp3 is not only a selective marker for a subset of ATLL but is also a possible pathogenic pathway of leukemia. [24][25][26]33 Foxp3 directly controls Treg cell function by interacting with the transcription factor AML1 and the Runx1 to suppress IL-2 and IFN-g production, upregulate Treg cell-associated molecules and exert suppressive activity. 27,34,35 The new antisense strategy, RNA interference (RNAi), is one of the most potent.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Furthermore, recent studies have found that one of the functions of FOXP3( þ ) ATLL cells is a Treg-like suppressive activity. [23][24][25][26] Roncador et al 22 reported that FOXP3 was a specific marker of ATLL in peripheral T-cell lymphoma. 22 We can therefore assume that some ATLL cells express FOXP3 and may be derived from Tregs.…”
mentioning
confidence: 99%
“…In hepatocellular carcinoma, high proportions of T regs within the liver are thought to precede the development of tumorigenesis and are associated with an unfavorable prognosis (22)(23)(24). Aggressive forms of adult T cell leukemia/lymphoma have been shown to up-regulate FoxP3 within the tumor cells themselves, conferring the ability of the tumor to actively suppress other lymphocytes (25). Bladder carcinomas have been found to be dominated by immunosuppressive regulatory T cells (26).…”
Section: Introductionmentioning
confidence: 99%